2022
DOI: 10.1097/nne.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning a Graduate Nursing Physical Examination Skills Lab to an Online Learning Modality

Abstract: Background: Continued restrictions imposed on face-to-face learning related to the SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) pandemic resulted in a decision to permanently transition a graduate nursing education advanced assessment course from a hybrid to an online learning modality. Purpose: The purpose of this article is to describe the transition of the physical examination skills lab from face-to-face to online, compare advanced practice nursing student performance outcomes, and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The majority of higher education institutions including health profession educators (HPEs) across the world had to transition from physical teaching and learning strategies to online strategies for emergency remote learning [ 4 ]. Continued pandemic restrictions imposed on face-to-face learning resulted in a decision to permanently transition a graduate nursing education advanced assessment course from a hybrid one to online learning [ 5 , 6 , 7 , 8 , 9 ]. With online learning, learning takes place partially or entirely over the Internet, making it an ideal course delivery model for adult learners wishing to develop new skills and competencies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of higher education institutions including health profession educators (HPEs) across the world had to transition from physical teaching and learning strategies to online strategies for emergency remote learning [ 4 ]. Continued pandemic restrictions imposed on face-to-face learning resulted in a decision to permanently transition a graduate nursing education advanced assessment course from a hybrid one to online learning [ 5 , 6 , 7 , 8 , 9 ]. With online learning, learning takes place partially or entirely over the Internet, making it an ideal course delivery model for adult learners wishing to develop new skills and competencies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two years, multiple publications have described elements of the successful shift by graduate nursing programs to virtual environments due to COVID-19, such as student clinicals using telehealth (Diegel-Vacek, et al, 2021), virtual patient simulations (Buterakos & Keiser, 2021), physical assessment evaluation (Barnes & Vance, 2022), and virtual student evaluation using objective structured clinical examinations (Luke, et al, 2021). A few studies have published positive findings regarding student satisfaction with the shift to virtual content delivery in undergraduate nurses (Farsi, et al, 2021; Riley, et al, 2021), although another recent study in India showed that medical and undergraduate nursing students were not satisfied with the switch to virtual education (Dutta, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%